The effect of Cr content on the corrosion resistance of WC-Ni-Cr-Mo composites. (February 2021) - Santos, R.F.; Rocha, A.M. Ferro; Bastos, A.C.; Cardoso, J.P.; Rodrigues, F.; Fernandes, C.M.; Sacramento, J.; Ferreira, M.G.S.; Senos, A.M.R.; Fonseca, C.; Vieira, M.F.; Malheiros, Luís F.
Abstract: Ni-Cr-Mo is a candidate to substitute Co binders in WC-based composites, where high corrosion resistance is required. This work focused on the effect of Cr on the corrosion susceptibility of WC-Ni-Cr-Mo composites, in acid media. Specimens were produced by powder metallurgy followed by microstructural, chemical and mechanical characterization. Open circuit potential measurements, potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) were employed to evaluate the corrosion susceptibility of WC-Ni-Cr-Mo alloys with different Cr content. The results highlight the greater aggressiveness of chloride medium compared to sulphate environment, and reveal that Cr can effectively decrease corrosion susceptibility without hampering the mechanical properties in both media, especially in chloride solution, where major improvements are observed. Highlights: Corrosion susceptibility of WC-Ni-Cr-Mo composite studied in acidic media. Chloride is more aggressive than sulphate to the binder phase. Cr additions up to 1.5 wt% substantially improve corrosion resistance. Cr/binder ratio < 11 wt% is insufficient for corrosion protection in chloride medium. Mechanical performance is not substantially hindered by Cr.